2005
DOI: 10.1557/jmr.2005.0120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotary-die equal channel angular pressing on the thermoelectric properties of a (Bi,Sb)2Te3 alloy

Abstract: A (Bi,Sb) 2 Te 3 alloy powder was sintered via a pulse discharge sintering process followed by a rotary-die equal channel angular pressing (ECAP) process. It was found by x-ray diffraction analysis that the as-sintered material shows preferentially orientated microstructure, which were considerably eliminated by following ECAP processes. Generally, the Seebeck coefficient of the material was reduced by ECAP processing, which was attributed to the increased carrier concentration after the severe plastic deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In the last few years, several studies have been made on applying ECAE or similar methods to the bismuth-telluride based materials. [7][8][9] We also had reported that applying the angular extrusion technique with rapidly solidified and stacked foils of bismuth-telluride based material was effective in improving the carrier mobility of the bismuth-telluride based material because of the fine orientated texture that is formed.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, several studies have been made on applying ECAE or similar methods to the bismuth-telluride based materials. [7][8][9] We also had reported that applying the angular extrusion technique with rapidly solidified and stacked foils of bismuth-telluride based material was effective in improving the carrier mobility of the bismuth-telluride based material because of the fine orientated texture that is formed.…”
Section: Introductionmentioning
confidence: 99%
“…3 Typically p-Bi x Sb 2Àx Te 3 and n-Bi 2 (Se y Te 3Ày ) are state-of-the-art materials for the 200-400 K temperature range. 4 The product of the figure of merit and temperature, ZT, at 300 K achieved so far is 1.14 for the p-type alloy (Bi 2 Te 3 ) 0.25 (Sb 2 Te 3 ) 0.72 (Sb 2 Se 3 ) 0.03 . 5 At low temperature, ZT of p-type CsBi 4 Te 6 is 0.8 at 225 K, 6 and single crystals of n-type Bi 1Àx Sb x alloys exhibit the optimum thermoelectric performance at 80 K. [7][8][9] Bi and Sb are semimetals, which both exhibit a similar rhombohedral crystal structure (the so-called A7 structure) of space group R 3m.…”
Section: Introductionmentioning
confidence: 87%
“…Some applications of thermoelectric refrigeration are in the cooling of CCDs, infrared detectors, laser diodes, and CMOS computer processors. [1][2][3][4] Cooling of laser diodes and infrared detectors to temperatures of 100 , T , 200 K would greatly improve the performance and sensitivity. 1,2 Moreover, if the cooling temperature can reach ;90 K, prospects of using thermoelectric refrigeration for superconducting electronics become feasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bonding becomes a cleavage plane that leads to strength reduction in the single crystal. To overcome the disadvantages presented by single crystals, many synthetic methods were employed to obtain Bi 2 Te 3 -based alloy bulks with higher mechanical strength and good thermoelectric properties; these methods include the Bridgman-Stockbarger method [20], equal channel angular pressing [21], hot pressing [22], hot extrusion [23,24], shear extrusion [25], and physical vapor deposition [26]. Using a two-step spark plasma sintering technique, researchers prepared textured n-type Bi 2 Te 3 with enhanced thermoelectric and mechanical properties; the authors indicated that controlling texture effectively improved the thermoelectric and mechanical properties of Bi 2 Te 3 -based materials [27].…”
Section: Bi-te Alloysmentioning
confidence: 99%